2014
DOI: 10.7554/elife.03399
|View full text |Cite
|
Sign up to set email alerts
|

A molecular mechanism of mitotic centrosome assembly in Drosophila

Abstract: Centrosomes comprise a pair of centrioles surrounded by pericentriolar material (PCM). The PCM expands dramatically as cells enter mitosis, but it is unclear how this occurs. In this study, we show that the centriole protein Asl initiates the recruitment of DSpd-2 and Cnn to mother centrioles; both proteins then assemble into co-dependent scaffold-like structures that spread outwards from the mother centriole and recruit most, if not all, other PCM components. In the absence of either DSpd-2 or Cnn, mitotic PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
238
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(254 citation statements)
references
References 77 publications
16
238
0
Order By: Relevance
“…A similar function had previously been proposed for PLP and Cnn in Drosophila; however, neither of these proteins have clear homologs in C. elegans [29,31]. Our findings are consistent with a recent report showing that, in Drosophila, SPD-2 works together with Cnn to recruit mitotic PCM to the mother centriole [32]. The total amount of SPD-2 in the cell had previously been suggested to limit PCM size in mitotic cells [33].…”
Section: Discussionsupporting
confidence: 92%
“…A similar function had previously been proposed for PLP and Cnn in Drosophila; however, neither of these proteins have clear homologs in C. elegans [29,31]. Our findings are consistent with a recent report showing that, in Drosophila, SPD-2 works together with Cnn to recruit mitotic PCM to the mother centriole [32]. The total amount of SPD-2 in the cell had previously been suggested to limit PCM size in mitotic cells [33].…”
Section: Discussionsupporting
confidence: 92%
“…However, the situation in flies seems to be a little more complex. Previously, in embryos, both Cnn and Spd-2 were shown to be initially recruited into a central region from where they subsequently moved outwards [5,6,16] ( Figure 1C). To address whether this behavior was specific to embryos or whether it also occurred in other cell types, Conduit and Raff [15] performed FRAP of Spd-2-GFP and GFP-Cnn at centrosomes in mitotic larval brain cells.…”
mentioning
confidence: 78%
“…These centrosomes contained intact centrioles surrounded by an extensive salt-resistant matrix that was capable of recruiting PCM components [3,4]. Early insights into the molecular composition of a PCM scaffold came from the identification of two key centrosomal proteins, Spd-2 and Centrosomin (Cnn) in flies and SPD-2 and SPD-5 in worms, which together form a scaffold around the mother centriole that recruits other PCM components [5][6][7][8][9]. Indeed, utilizing an in vitro PCM assembly system, Woodruff et al [10] recently reported that recombinant SPD-5 polymerizes in a concentration-and time-dependent manner to form micrometer-sized porous networks.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning live applications, SIM may involve 2D and 3D subdiffraction resolution of widely spread intracellular structures such as plasmodesmata 34 or cell walls 35 and simultaneous dual-color time-lapse imaging of actin and clathrin-coated vesicles 36 . Of particular importance was the recent implementation of fluorescence recovery after photobleaching analysis during SIM time-lapse imaging 37 .…”
Section: Applications Of the Methodsmentioning
confidence: 99%